2013
DOI: 10.4161/sgtp.23477
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Rab and Arf GTPases regulate endosomal phosphatidylinositol-4,5-bisphosphate during endocytic recycling

Abstract: A fter endocytosis, a selective endocytic recycling process returns many endocytosed molecules back to the plasma membrane. The RAB-10/Rab10 GTPase is known to be a key recycling regulator for specific cargo molecules. New evidence, focused on C. elegans RAB-10 in polarized epithelia, points to a key role of RAB-10 in the regulation of endosomal phosphatidylinositol-4,5-bisphosphate (PI(4,5)P2) levels. In turn, PI(4,5)P2 levels strongly influence the recruitment of many peripheral membrane proteins, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
(37 reference statements)
2
13
0
Order By: Relevance
“…activities. Previous studies suggest that dual or shared effectors represent a point of convergence of Rab, Arf, and Arl signals in membrane traffic (Burguete et al, 2008;Shi and Grant, 2013). In line with this, we noted that recently characterized Rab7 effector, PLE KHM1, shares ∼40% similarity over the length of its RUN domain with the known Arl8b effector SKIP.…”
Section: Introductionsupporting
confidence: 84%
“…activities. Previous studies suggest that dual or shared effectors represent a point of convergence of Rab, Arf, and Arl signals in membrane traffic (Burguete et al, 2008;Shi and Grant, 2013). In line with this, we noted that recently characterized Rab7 effector, PLE KHM1, shares ∼40% similarity over the length of its RUN domain with the known Arl8b effector SKIP.…”
Section: Introductionsupporting
confidence: 84%
“…S1, L and M). CNT-1 acts as an ARF-6 GAP, modulating ARF-6 activity and maintaining levels of the lipid PI(4,5)P2 on these endosomes ( Shi et al, 2012 ; Shi and Grant, 2013 ). Consistent with a loss of RAB-10 activation, we found that CNT-1-GFP labeling became diffusive in let-413(ycx23) or let-413(RNAi) animals, with a distinct loss of CNT-1 from punctate endosomes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…32 RAB10 has been localized to many organelles, such as endoplasmic reticulum (ER), Golgi, early endosomes, and recycling endosomes, and mediates membrane trafficking within the cell partly by regulating endosomal phosphatidylinositol-4,5-bisphosphate levels. 33,34 Together, these data reveal a novel theme of mTOR function by regulating a series of proteins being specifically involved in endocytosis and vesicle transport.…”
Section: Discussionmentioning
confidence: 99%